Development of Crimping Trainer Learning Media in Basic Computer and Networking Subjects at Senior High School: Pengembangan Media Pembelajaran Trainer Crimping pada Mata Pelajaran Komputer dan Jaringan Dasar di Sekolah Menengah Atas - Muhammad Irfan Jazuli; Rahmania Sri Untari (Universitas Muhammadiyah Sidoarjo, 2022)
This study develops a novel trainer learning media for computer subjects and basic networking, targeting class XI Computer and Network Engineering students. Employing the Research and Development (R&D) approach with the ADDIE model, the study demonstrates the suitability of the developed media through expert assessments. Validation scores of 90% and 93% from media and material experts respectively affirm its effectiveness. The trainer learning media enhances computer and network learning at SMK Yapenas Gempol, class XI, contributing to educational technology advancement in the field. Highlights: Development of innovative learning support: This study focuses on developing a trainer learning media with new innovations, aiming to enhance the learning experience for computer subjects and basic networking. Feasibility assessment: The research employs the ADDIE model and involves experts' evaluation to determine the suitability of the developed learning media for classroom implementation, with high validation scores obtained from both media and material experts. Implications for Computer and Network Engineering education: The findings of this study have significant implications for the field of Computer and Network Engineering, contributing to the advancement of educational technology and providing a valuable tool to support teaching and learning processes. Keywords: Trainer learning media, computer subjects, basic networking, Research and Development (R&D), feasibility.